FAKTOR YANG MEMPENGARUHI KEJADIAN STUNTING PADA ANAK USIA 2-5 TAHUN DI KEPULAUAN MANDANGIN - Oktavianisya, Nelyta; Sumarni, Sri; Aliftitah, Sugesti (Universitas Tribhuwana Tunggadewi, 2021)
Stunting is a linear growth disorders, caused by chronic malnutrion of nutrient intake or chronical nor recurrence infectious diseases. The aim of this study was to analize factors related to stunting on 2-5 years old children. This study was analytic study with case control approach. The population of this study were every mother of children with 2-5 years age who lived in Pulau Mandangin in 2019. Case group were mother of children with 2-5 years ages with stunting (76 respondents). Control group were mother of children with 2-5 years ages without stunting (152 respondents). Simple random sampling technic was used on sample retrieval and data retrieval using questioner. The data analized by using univariate, bivariate (chi-square) and multivariate analysis with logistic regression test.The study result showed that related variable to stunting were low birth weight baby (0,015), Genetic history (0,008), nutrient intake (0,011), exclusive breast milk (0,004), and environment (0,009). The result of multivariate analysis nutrient intake had great risk of stunting (OR=4,0). Nutrient intake is dominant factors related to stunting. there was influence of low birth weight status, genetic, exclusive breast milk, nutrient intake and environment. While economic status was not related to stunting incident on children with ages 2-5 years.